The role of health care services in assisting victims of crime - Vidaković Ivana M. (Temida)
In the first, preparatory phase for establishing the Victim Support Service for crime victims in Serbia the author interviewed medical/health care professionals which, in their work, dealing with victims of crime. In this paper the author will present general observation of the situation and expressed views about this phenomenon. Special emphasize will be on a shortages in actual practice and possible solutions for its improvement. In the conclusion the author will point out the need for sensibilization and education of majority of medical professionals and the broader media approach in order to perceive and recognize problems in the community and professional groups which are working with victims of crime.